Step-by-step explanation:
![{:}\hookrightarrow\sf \dfrac {1}{4}\div \dfrac {9}{10}](https://tex.z-dn.net/?f=%7B%3A%7D%5Chookrightarrow%5Csf%20%5Cdfrac%20%7B1%7D%7B4%7D%5Cdiv%20%5Cdfrac%20%7B9%7D%7B10%7D)
![{:}\hookrightarrow\sf \dfrac {1}{4}\times \dfrac {10}{9}](https://tex.z-dn.net/?f=%7B%3A%7D%5Chookrightarrow%5Csf%20%5Cdfrac%20%7B1%7D%7B4%7D%5Ctimes%20%5Cdfrac%20%7B10%7D%7B9%7D)
![{:}\hookrightarrow\sf \dfrac {10}{36}](https://tex.z-dn.net/?f=%7B%3A%7D%5Chookrightarrow%5Csf%20%5Cdfrac%20%7B10%7D%7B36%7D)
![{:}\hookrightarrow\sf \dfrac {5}{18}](https://tex.z-dn.net/?f=%7B%3A%7D%5Chookrightarrow%5Csf%20%5Cdfrac%20%7B5%7D%7B18%7D)
Answer:
chord CD is 11
Step-by-step explanation:
just add 2 and 9
Answer:
B'(16,14)
Step-by-step explanation:
First find the coordinates of the vertex B. The center of the square M is the midpoint of the diagonal AC. Since A(2,7) and C(8,1), the center has coordinates
![M\left(\dfrac{2+8}{2},\dfrac{7+1}{2}\right)=M(5,4).](https://tex.z-dn.net/?f=M%5Cleft%28%5Cdfrac%7B2%2B8%7D%7B2%7D%2C%5Cdfrac%7B7%2B1%7D%7B2%7D%5Cright%29%3DM%285%2C4%29.)
Point M is also the midpoint of the diagonal BD. Let B has coordinates (x,y), then
![\dfrac{x+2}{2}=5\Rightarrow x=8,\\ \\\dfrac{y+1}{2}=4\Rightarrow y=7.](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%2B2%7D%7B2%7D%3D5%5CRightarrow%20x%3D8%2C%5C%5C%20%5C%5C%5Cdfrac%7By%2B1%7D%7B2%7D%3D4%5CRightarrow%20y%3D7.)
Hence, B(8,7).
Now, the dilation by a scale factor 2 with the center of dilation at the origin has the rule
(x,y)→(2x,2y).
Thus,
B(8,7)→B'(16,14).
(boys) x=3(y)
(girls) y=x/3
Step-by-step explanation:
Answer: r = 2/3
Step-by-step explanation:
In a geometric sequence, the consecutive terms differ by a common ratio. The formula for determining the nth term of a geometric progression is expressed as
Tn = ar^(n - 1)
Where
a represents the first term of the sequence.
r represents the common ratio.
n represents the number of terms.
From the information given,
a = 36
The 4th term is 32/3
n = 4
Therefore,
T4 = 32/3 = 36 × r^(4 - 1)
32/3 = 36 × r^3
Dividing both sides if the equation by 36, it becomes
32/3 × 1/36 = r^3
8/27 = r^3
Taking cube root of both sides of the equation, it becomes
(8/27)^1/3 = r^3 × 1/3
r = 2/3